(untitled) (CIPEEX, 2025)
The research in question aims to present a pioneering approach to the Sociological Dimension as a Reading of Reality. The objectives outlined are clear, relevant and aimed at an in-depth understanding of the importance of this specific topic. The bibliographic review method provided the opportunity for research based on a solid theoretical foundation, guaranteeing the consistency of the results obtained. During the development of the study, the results are presented in a clear and sufficient manner, enabling a thorough analysis and a broad understanding of the data collected and the conclusions reached. Also noteworthy is the methodological rigor used, which ensures the reliability and validity of the results found. The impact of the research is significant in both the scientific and social spheres. From a scientific point of view, it contributes to the advancement of sociological knowledge, offering new perspectives and insights for future research in this area. In the social context, the results obtained have important practical implications, providing support for the formulation of more effective public policies aimed at the real demands of society. In summary, the research stands out for its originality, clarity and relevance of objectives, consistent theoretical and methodological foundation, adequate presentation of results and significant scientific and social impact, consolidating itself as a relevant contribution to the field of sociology and understanding of contemporary social dynamics.